Analisis Penggunaan Sumber Belajar pada Materi Ekosistem Darat di SMAN Insana Barat dan SMK St. Agustinus Kefamenanu - Masing, Feliksitas Angel (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2019)
This study aims to know: (1) learning resources used in the learning of terrestrial ecosystem biology material in SMAN Insana Barat School, and (2) learning resources used in the learning of terrestrial ecosystem biology material at St. Augustine School Kefamenanu. This research is a type of survey research. The study population was biology teachers at SMAN Insana Barat School and St. Augustine School Kefamenanu. This research was conducted in January-March 2019. Data collection techniques used questionnaires on land ecosystem learning resources. Data analysis techniques used qualitative descriptive statistics. The results of the study show that: (1) the learning resources used in learning Biology on terrestrial ecosystems in SMAN Insana Barat School consist of direct objects, most of which are artificial ecosystems while indirect objects are mostly presented in textbooks, textbooks, and print modules. For learning resources in the form of E-modules and the internet and other learning resources, they have not been used by SMAN Insana Barat. This is because the availability of wifi in schools is inadequate. (2) Learning resources used in learning biology of terrestrial ecosystems at St. Augustine School Kefamenanu.consists of direct objects which are mostly in the form of artificial ecosystems while indirect objects are mostly presented in textbooks, textbooks, and printed modules. For learning resources in the form of E-modules and internet as well as other learning resources, it has not been used by the teachers and student from SMAN Insana Barat School and St. Augustine School Kefamenanu East Nusa Tenggara. This is because the availability of wifi in schools is inadequate.